A New Species of the Genus Hemirhopalum (Coleoptera, Dermestidae) from Bolivia - Háva, J. (Вестник зоологии, 2013)
Hemirhopalum alleni Hava, sp. n. from Bolivia (South America) is described, illustrated and compared with two similar species: Hemirhopalum bicolor Sharp, 1902 and H. brasiliense Herrmann et Hava, 2013. Описан Hemirhopalum alleni Hava, sp. n. из Боливии. Приведены его иллюстрации и сравнение с двумя сходными видами: Hemirhopalum bicolor Sharp, 1902 and H. brasiliense Herrmann et Hava, 2013.